Ventral striatal dopamine transporter availability is associated with lower trait motor impulsivity in healthy adults. Issue 1 (December 2018) - Smith, Christopher; San Juan, M.; Dang, Linh; Katz, Daniel; Perkins, Scott; Burgess, Leah; Cowan, Ronald; Manning, H.; Nickels, Michael; Claassen, Daniel; Samanez-Larkin, Gregory; Zald, David
Abstract Impulsivity is a transdiagnostic feature of a range of externalizing psychiatric disorders. Preclinical work links reduced ventral striatal dopamine transporter (DAT) availability with heightened impulsivity and novelty seeking. However, there is a lack of human data investigating the relationship between DAT availability, particularly in subregions of the striatum, and the personality traits of impulsivity and novelty seeking. Here we collected PET measures of DAT availability (BPND ) using the tracer18 F-FE-PE2I in 47 healthy adult subjects and examined relations between BPND in striatum, including its subregions: caudate, putamen, and ventral striatum (VS), and trait impulsivity (Barratt Impulsiveness Scale: BIS-11) and novelty seeking (Tridimensional Personality Questionnaire: TPQ-NS), controlling for age and sex. DAT BPND in each striatal subregion showed nominal negative associations with total BIS-11 but not TPQ-NS. At the subscale level, VS DAT BPND was significantly associated with BIS-11 motor impulsivity (e.g., taking actions without thinking) after correction for multiple comparisons. VS DAT BPND explained 13.2% of the variance in motor impulsivity. Our data demonstrate that DAT availability in VS is negatively related to impulsivity and suggest a particular influence of DAT regulation of dopamine signaling in VS on acting without deliberation (BIS motor impulsivity). While needing replication, these data converge with models of ventral striatal functions that emphasize its role as a key interface linking motivation to action.